Effects of race distance on physical, hematological and biochemical parameters of endurance horses - Adamu, Lawan; Mohd Adzahan, Noraniza; Abdullah, Rasedee; Fateh Mohamed, Bashir Ahmad (Science Publications, 2010)
Problem statement: Endurance horses are generally exposed to severe stress during endurance competitions. These horses are however conditioned to cover the long distances of the competitions at moderate speeds. Approach: This study was conducted in Malaysia to determine the post-race hematological, blood electrolyte and biochemical and physical parameters of horses of 40, 80 and 120 km endurance race categories and eliminated and horses that completed the races with good performance. Whole blood, plasma and serum samples were collected after each race. Results: After physical examination 7 (9.72%) 120 km-, 48 (66.67%) 80 km- and 17 (23.61%) 40 km-race horses were eliminated. Eight horses, all from the 80 km-race category completed the race with good performance. The mean heart of the good performance horses (74.2±13.9 beats min-1) was higher than that of the eliminated 40 km- (68.2±14.7 beats min-1), 80 km-race (62.9±9.7 beats min-1) horses. The blood lactate concentration of good performance horses was 9.2±2.2 mmol L-1, which was significantly higher than in the 40 km- (6.0±2.9 mmol L-1), 80 km- (6.7±3.2 mmol L-1) and the 120 km-race (6.4±1.6 mmol L-1) horses. The blood glucose concentration was lower in the good performance horses (1.6±0.9 mmol L-1) than the eliminated 40 km- (5.7±1.9 mmol L-1), 80 km- (4.3±2.4 mmol L-1) and the 120 km-race (5.0±1.4 mmol L-1) horses. Conclusion: The study showed that eliminated horses exhibited poorer glucose utilization than good performance horses, which may have resulted in poor lactate production. Thus the blood lactate and glucose concentrations of horses during training may be used to predict their performance in endurance races.